2022
DOI: 10.3390/curroncol29100591
|View full text |Cite
|
Sign up to set email alerts
|

Peripheral Blood Cell Ratios as Prognostic Indicators in a Neoadjuvant Chemotherapy-Treated Breast Cancer Cohort

Abstract: Breast cancer represents a heterogeneous condition in which the interaction between host immune response and primary oncogenic events can impact disease progression. Ratios of systemic blood-based immunocytes have emerged as clinically-relevant prognostic biomarkers in cancer patients. The NLR (neutrophil-to-lymphocyte ratio) has been shown to be prognostic in a variety of cancers, including breast cancer. However, evaluation of the prognostic value for overall survival (OS) and disease-free survival (DFS) of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 28 publications
0
2
0
Order By: Relevance
“…Therefore, in-depth studies targeting this area are beneficial to further reveal the pathogenesis of breast cancer and to improve its prevention and treatment measures. Peripheral blood leukocyte count is a routine clinical test, which is mainly used for the assessment of patients’ general condition and the diagnosis of acute bacterial infections, with the characteristics of being easy to perform and low cost 50 , 51 . As important immune cells in the organism, the levels of various leukocytes in peripheral blood can also reflect changes in immune function.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, in-depth studies targeting this area are beneficial to further reveal the pathogenesis of breast cancer and to improve its prevention and treatment measures. Peripheral blood leukocyte count is a routine clinical test, which is mainly used for the assessment of patients’ general condition and the diagnosis of acute bacterial infections, with the characteristics of being easy to perform and low cost 50 , 51 . As important immune cells in the organism, the levels of various leukocytes in peripheral blood can also reflect changes in immune function.…”
Section: Discussionmentioning
confidence: 99%
“…Pretreatment neutrophil-to-lymphocyte ratio (NLR) and platelet-tolymphocyte ratio (PLR) and other immune and inflammatory biomarkers have been reported to be independent predictors of breast cancer prognosis (13)(14)(15). It was observed that these easy-toobtain, non-invasive, and individualized peripheral blood biomarkers are of great prognostic value in numerous tumors including breast cancer, and increased NLR and PLR and decreased ALC may be associated with poor prognosis (16,17). However, several previous meta-analyses only focus on breast cancer, and thus, there is still great uncertainty for the values of these potential prognostic biomarkers in MBC (2).…”
Section: Introductionmentioning
confidence: 99%